BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS FACING THE CORONAVIRUS DISEASE-19 OUTBREAK IN PURWOSARI VILLAGE - Ayasti, Erlin Cindy; Nugroho, Agung; Fah, Lay Yoon (Universitas Muhammadiyah Purwokerto, 2022)
This research is motivated by the importance of student behavior in mitigating the COVID-19 disaster. As the number of positive cases continues to grow, it is necessary to take steps to prevent COVID-19. This study discusses the analysis of student behavior, especially in elementary schools in dealing with the Coronavirus Disease-19 outbreak. The purpose of this study was to determine the behavior of elementary school students during the COVID-19 pandemic and the factors that influence it. To answer the objectives of the researcher used a descriptive study and qualitative analysis. Data collection techniques using interviews, observation and documentation. The research subjects were fifth grade students and fifth grade students' parents. Data analysis used data collection, data reduction, data display and conclusion drawing. Test the validity of the data using triangulation of sources and techniques. The results of the research at the beginning of the pandemic were that students took steps to prevent COVID-19, namely 1) washing hands, 2) wearing masks, 3) keeping as much distance as possible, 4) reducing as much, 5) reducing mobility. Meanwhile, currently students are no longer taking COVID-19 prevention measures, namely 1) not washing their hands, 2) not wearing masks, 3) not keeping their distance, 4) not limiting them, 5) not reducing mobility. Internal factors that influence student behavior at the beginning of the pandemic are fear and external factors, namely 1) family environment, 2) school environment, 3) media. Meanwhile, currently internal factors that influence student behavior are 1) boredom, 2) laziness, external factors that influence are 1) family environment, 2) community environment